Mining or industrial activity? The Legal Qualification of the Cement Manufacturing Process and the Bet for a Certain Normative Framework that Clarifies the Competences of the Ministry of Energy and Mines and the Ministry of Production - Palomino Seguín, Daniel Jesús (2014)
Mining or industrial activity? This is not only an ancient question in Peruvian mining sector but a key issue for domestic and foreign private investment on cement. Since few years ago, cement manufacturing process has been being qualified and regulated by the Peruvian Mining Authority as a mining benefit process which implies the obligation to obtain a benefit mining concession previously. However, upon a review of the technical process aspects, the legal framework in force and a recent judgment enacted by the Constitutional Court of Peru regarding this topic, the position traditionally assumed by the Ministry of Energy and Miningcould be reconsidered.